Theological Comments Mentioned in Jamiâ€™ al-Tirmidzi and Its Application in Achieving Acceptance and Understanding Within Muslim Community - Fouly, Nabil (IAIN Surakarta, 2018)
This is a study of the theological comments ofÂ Imam TirmidziÂ and those of which he mentioned in his book â€œal-Jamiâ€™ al-Kabirâ€.Â These comments provide us a picture of how the early generations ofÂ IslamÂ dealt with the issues related to Creed andÂ Aqeda,Furthermore the issue of scarcity of views and comments associated to the earlygenerations ofÂ IslamÂ in dealing the issues of Creed andÂ AqedaÂ is also dealt with in this study.Â Most of the comments ofÂ at-TirmidziÂ in the study are mentioned as exact quotations and then they are classified according to the topics they are related to, and after classification analysis of the content along with the methodology and inclination ofthe holder of the opinion regarding these issues ofÂ AqedaÂ is studied. The study shows that the issue which overwhelmed and kept the early generation of Islam occupied was the issue ofÂ amal(Actions) related to those issues of creed or in other words theywere more interested in the actions which has to exist as a result of thatÂ aqedahÂ hence those whose thoughts and emotions are attached to these early generations ofÂ IslamÂ have to follow them in their pursuit of actions more than any other thing. Moreover regarding the conception of anthropomorphistic attributes the study yields that the more accurate and sound opinion associated to the early generations in this regard in the opinion ofÂ Tafwedhi.e to depute the knowledge of its meaning to Godalone and that on extremely rare occasions they use to incline towards theirÂ taweeli.e metaphorical interpretation. And this last issue in particular must and should be discussed within scholarly circles only and the general public should refrain from indulging themselves in such technical issues.Â